Challenges, applications and future directions of precision medicine in prostate cancer – the role of organoids and patient‐derived xenografts. (30th May 2020) - Joshi, Andre; Roberts, Matthew J.; Alinezhad, Saeid; Williams, Elizabeth D.; Vela, Ian
Abstract : Objective: To provide a clinically relevant outline of various current precision medicine principles and available evidence on the application and potential for a precision medicine approach in prostate cancer. Methods: Narrative review of the current literature in the field. Conclusion: Precision medicine is the concept of individualising patient management based on specific tumour characteristics and biology, rather than traditional histological subtypes. The overall aim is to personalise management to individual patients, to provide the right cancer treatment, to the right patient, at the right time. While the approach aims to improve clinical outcomes, decrease morbidity and improve survival in men with advanced prostate cancer, its clinical application is in its infancy. It does however show great promise in this and other cancers, and will continue to be an area of active research and clinical investigation.